PROFILE OF CREATIVE THINKING ABILITIES IN CLASS VII STUDENTS OF SMPN I ADONARA BARAT - Maria Angelina Peurape; Aloisius Harso; Daniel Wolo (Program Studi Pendidikan IPA FKIP Universitas Jember, 2020)
This study aims to determine the profile of the ability to think creatively in Science in grade VII Students of SMPN I Adonara Barat. This type of research is descriptive research. The population to 70 students, and the sample in the study was class VII A students totaling 30 students who were obtained by purposive sampling technique. Data collection using a questionnaire. The results showed that students creative thinking abilities were categorized as quite creative (47.7%). This is evidenced by the results of the descriptive analisis of the student questionnaire, namely that they are less creative (63%), higher than the number of students who are categorized as very creative (6.7%), creative (13,3%) and quite creative (17%).